Religious Education in the European Educational Space: Social and Cultural Context - Lomachinska, Irina; Martych, Ruslana (Studia Warmińskie, 2021)
The article studies the features of religious education in the context of modern changes in the contemporary European educational space. Based on the analysis of Western European educational models – non-denominational, denominational, multi-denominational and mixed – the main problems of education about religions, which are inherent in the Ukrainian educational system, have been determined. The conclusions emphasize that although due to historical, social and religious-cultural peculiarities there are no unified approaches to the study of religions, the purpose should be the establishment of spiritual values, the search for worldviews based on dialogue and tolerance. Among educational technologies, the most optimal are surveys, discussions and debates involving analytical tools.